Tracking the push towards extinction: combining dispersal and management data to monitor Asian longhorned beetle eradication in the U.S. - Trotter, Robert Talbot; Ryan, Josie K.; Chandler, Jennifer L.; Pfister, Scott (Frontiers in Insect Science, 2023)
Introduction Based on the threat posed by the Asian longhorned beetle (Anoplophora glabripennis Motschulsky), many countries including the United States have adopted policies of eradication. The eradication of infestations that cover hundreds of square kilometers can require multiple visual surveys of millions of individual trees. At these scales, eradication may take several decades and span multiple beetle generations. During this period the infestation of new trees adds spatially-explicit risk to the landscape while surveys and the removal of infested trees reduce it. Methods To track dynamic risk on the landscape we have developed the Asian Longhorned Beetle Hazard Management and Monitoring Tool. The geospatial tool combines data documenting; the locations, levels of infestation, and dates of detection of infested trees; the locations, methods, and timing of survey and host removal activities; and a reconstruction of beetle movement within the infested landscape to generate annual spatial estimates of infestation risk based on the combination of beetle dispersal and survey and host removal activities. Results The analyses of three eradication programs highlight similar patterns in risk through time with risk peaking at the time infestations are detected and declining as management activities slow beetle spread and reduce risk through surveys. However, the results also highlight differences in risk reduction among the eradication programs associated with differences in beetle dispersal among infestations and the size of the infested landscape, highlighting the importance of applying local information to structure eradication programs. Discussion The Asian Longhorned Beetle Hazard Management and Monitoring Tool provides a quantitative repeatable approach to tracking changes in infestation risk using local beetle behavior and management efforts. In addition to this, the tool may provide a structure to optimize eradication efforts by allowing managers to estimate expected risk reduction based on proposed survey and host removal strategies.